2017
DOI: 10.1016/j.jped.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the laryngeal mask airway for surfactant administration in neonates

Abstract: Surfactant administration by LMA showed short-term efficacy, with similar supplementary oxygen need compared to surfactant by ETT, and lower MV requirement. Further studies with larger sample size are necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…LMA is used for both adult and children's anaesthesia and is the initial adjunctive airway device recommended by the American Society of Anaesthesiologists' di icult airway algorithm (Apfelbaum 2013). LMA use has also been tested in preterm neonates in nonresuscitation settings for surfactant administration to avoid endotracheal intubation (Barbosa 2012;Barbosa 2017;Pinheiro 2016;Wanous 2017). In a review on supraglottic airway devices during neonatal resuscitation Schmolzer 2013 included four trials that compared positive pressure ventilation delivered by an LMA versus bag and mask or an endotracheal tube.…”
Section: Description Of the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMA is used for both adult and children's anaesthesia and is the initial adjunctive airway device recommended by the American Society of Anaesthesiologists' di icult airway algorithm (Apfelbaum 2013). LMA use has also been tested in preterm neonates in nonresuscitation settings for surfactant administration to avoid endotracheal intubation (Barbosa 2012;Barbosa 2017;Pinheiro 2016;Wanous 2017). In a review on supraglottic airway devices during neonatal resuscitation Schmolzer 2013 included four trials that compared positive pressure ventilation delivered by an LMA versus bag and mask or an endotracheal tube.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Study used LMA for surfactant administration in non-resuscitation settings Barbosa 2017 Study used LMA for surfactant administration in non-resuscitation settings.…”
Section: Participantsmentioning
confidence: 99%
“…The laryngeal mask airway, a supraglottic airway device, may be used as an interface to deliver surfactant. [42][43][44][45] However, there is currently no device available for use in very low birth weight (BW) infants, who constitute the majority of infants diagnosed with RDS.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the use of antenatal steroids were reported in five studies and were comparable. [11][12][13][14][15] Birth weight and gestational age were comparable between LMA and control group for each study. Mode of delivery was reported to be similar between groups in four studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Mode of delivery was reported to be similar between groups in four studies. [12][13][14][15] Three studies reported no significant difference in respiratory distress score between intervention groups. 13,15,16 The time for enrollment of infants reported in five studies varied between 4 and 72 hours of life.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%